Vaccine Coverage Rates Among 12-23 Month Old Children Living in Four Selected Provinces of Turkey: Results of a Lot Quality Survey. - Üner, Sarp; Özelçi, Pervin; Çom, Seracettin; Kosdak, Mustafa; Mollahliloglu, Salih; Erkoç, Yasin (Turkiye Klinikleri Journal of Medical Sciences, 2012)
Objective: Revision surgery in bariatric surgery is becoming an important issue. It has been associated with higher complication rates, and there is no consensus on the standardized surgical approach to revision surgery. The aim of this study was to review the revision procedures performed in our institute. Material and Methods: A retrospective review of a prospectively maintained database was performed. One hundred thirty three operations were performed for morbid obesity. Primary procedures were laparoscopic adjustable gastric banding (LAGB) in 61 patients, vertical band gastroplasty (VBG) in 24 patients, Roux-en-Y gastric bypass in 21 patients, sleeve gastrectomy in 10 patients and biliopancreatic diversion with duodenal switch in six patients. Eleven patients were re-operated due to mechanical complications or inadequate weight loss. Data including age, gender, preoperative weight, body mass index (BMI) and postoperative complications were reviewed for all patients undergoing a revision procedure. Results: In patients with previous VBG, failure of weight loss (3/4) and outlet stenosis (1/4) were the indications. In patients with previous LAGB, mechanical side effects were the indications of surgery. The gastrocolic fistula was the indication of surgery in patient who had been revised from VBG to sleeve gastrectomy. At the mean follow-up of 13 months, the mean BMI and percentage of excess BMI were 32.3 kg/m2 and 37.4%, respectively. There was one stapler-line leakage. Conclusion: Our study suggests that revision bariatric surgery can be performed with satisfactory short-term weight loss. The knowledge of the potential complications associated with revision surgery and their management is crucial for patients' safety.